Economic impact of ethanol production on U.S. livestock sector: a spatial analysis of corn and distillers grain shipment - N'Guessan, Yapo Genevier (Kansas State University, 2007)
The production of corn-based ethanol in the U.S. has increased from 1,630 million gallons in 2000 to 4,855 million gallons in 2006, representing a 198% growth over the period considered. This growth is favored by the availability of more efficient technologies in the production process of ethanol and is sustained by the high prices of ethanol in the market. The industry is also supported by a favorable public policy, expressed in the form of laws, mandating an increase in the use of ethanol, and also in the form of tax incentives. The tremendous increase in the use of corn for the ethanol industry is made at the expense of the livestock industry that was the traditional destination for much of the U.S. corn grain. As the ethanol industry continues to expand, concerns are raised in regard to its impact as more and more corn is diverted from the livestock sector. This study investigates the economic impact of the ethanol industry on the U.S. livestock sector. Specifically, a shipping cost model is developed to simulate the impact of the ethanol industry on the shipping cost of corn at the national and individual state levels. The dynamics for major livestock producing states are also analyzed at the crop reporting district level. Different scenarios based on assumptions on the availability of corn and the production capacities of the ethanol industry are displayed. Results from the model indicate that nationwide there is a 5 to 22% increase in the shipping cost of corn for the livestock industry due to the ethanol industry, depending on the scenario involved. At the state level, there is an increase in the transportation cost for most of the states, with shipping cost doubling in some cases. Nevertheless, some states benefit from the dynamics created by the development of ethanol plants and are experiencing a reduction in their livestock industry corn transportation cost.
Keywords: Ethanol; Corn; Livestock; Economic; Impact; Shipment; Economics, Agricultural (0503)